1993
DOI: 10.1002/1097-0142(19930901)72:5<1631::aid-cncr2820720523>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of computed tomography in patients with peritoneal carcinomatosis

Abstract: Background. Radiologic tests to determine the size and location of cancer on peritoneal surfaces are needed for patient management and for clinical research activity. Methods. Computed tomography (CT) of the abdomen and pelvis were obtained on 45 patients with a diagnosis of peritoneal carcinomatosis before implementation of a complete exploratory laparotomy with biopsy or resection of all tissues suspicious of malignancy. CT findings and surgical findings were recorded and the data analyzed by dividing the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
19

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 242 publications
(109 citation statements)
references
References 14 publications
2
88
0
19
Order By: Relevance
“…12 However, the sensitivity of CT in the diagnosis of peritoneal carcinomatosis is generally low and is related to the tumor size; it ranges from 28% for implants <0.5 cm to 57% and 79% with larger tumor implants. 13 Transabdominal ultrasound can also be used to detect the presence of intraperitoneal fluid, depending on the location of the fluid in the abdominal cavity; however, it usually requires an accumulation of several hundred milliliters of fluid before ascites can be observed. 14 EUS has been reported to be more sensitive for the detection of ascitic fluid.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, the sensitivity of CT in the diagnosis of peritoneal carcinomatosis is generally low and is related to the tumor size; it ranges from 28% for implants <0.5 cm to 57% and 79% with larger tumor implants. 13 Transabdominal ultrasound can also be used to detect the presence of intraperitoneal fluid, depending on the location of the fluid in the abdominal cavity; however, it usually requires an accumulation of several hundred milliliters of fluid before ascites can be observed. 14 EUS has been reported to be more sensitive for the detection of ascitic fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Jacquet et al [11] demonstrated that diagnostic imaging showed only 50% accuracy for lesions from 0.5 to 5 cm in diameter, while above 5 cm the accuracy was 90%. Exploratory laparoscopy is a less invasive method to assess PM than open laparotomy, and laparoscopy matches laparotomy in capacity to diagnoste PM [12].…”
Section: Discussionmentioning
confidence: 99%
“…These observations were prospectively recorded for the CT and were compared to those observed at the time of abdominal exploration and during the cytoreductive surgical procedure. Figure 6 shows the results of this study [15].…”
Section: Prior Surgical Score (Pss)mentioning
confidence: 93%